50 Effects of post-weaning supplementation of immunomodulatory feed ingredient on body weight and cortisol levels in programmed fed beef heifers. (29th July 2019) - Danielo, Jessica L; Tipton, Jessie; Ricks, Ralph; McCarty, Keelee J; Long, Nathan
Abstract: The objective of this study was to determine the effects of an immunomodulatory feed ingredient during post-weaning on growth and cortisol levels of beef heifers. Commercial Angus heifers (n = 72) from two AI sires were blocked (n = 9) by sire and BW and then randomly assigned to one of two pens per block. Each pen (4 heifers/pen) per block was assigned to one of the treatments. Heifers were fed a commercial TMR twice daily from d 0 to 60 to gain 0.75 kg/day. The feed was top-dressed once a day with either 72g of Celmanax (CEL) or 72g of corn germ (CON) per pen. Body weight was collected on d -1, 0, 15, 30, 45, 60 and 61. Blood samples were collected on d 0, 15, 30, 45 and 60. Sixteen heifers (n = 8 CEL; n = 8 CON) were randomly selected for a corticotropin releasing hormone/ arginine vasopressin (CRH/AVP) challenge after the 60 d period. Two heifers per pen (n = 32) were randomly selected for a transportation challenge to evaluate stress response on d 61 or 62 of the study. Pen was the experimental unit and data was analyzed by ANOVA or repeated measures analysis as appropriate. Feed efficiency and BW gain was increased (P = 0.04) in CEL heifers compared to CON heifers. Serum cortisol concentrations were decreased (P < 0.01) in CEL heifers compared to CON heifers on d 30 to 60 post-weaning. Serum cortisol concentrations were decreased (P < 0.05) in CEL heifers compared to CON heifers during the CRH/AVP challenge from 60 to 150 minutes post infusion. Serum cortisol concentrations were decreased (P < 0.05) in CEL heifers compared to CON heifers throughout the transportation challenge. In summary, supplementation of Celmanax post-weaning increased BW gain and reduced cortisol concentrations in beef heifers.